Systematic characterization of Ustilago maydis sirtuins shows Sir2 as a modulator of pathogenic gene expression - Navarrete, Blanca; Ibeas, José I.; Barrales, Ramón R. (Frontiers in Microbiology, 2023)
Phytopathogenic fungi must adapt to the different environmental conditions found during infection and avoid the immune response of the plant. For these adaptations, fungi must tightly control gene expression, allowing sequential changes in transcriptional programs. In addition to transcription factors, chromatin modification is used by eukaryotic cells as a different layer of transcriptional control. Specifically, the acetylation of histones is one of the chromatin modifications with a strong impact on gene expression. Hyperacetylated regions usually correlate with high transcription and hypoacetylated areas with low transcription. Thus, histone deacetylases (HDACs) commonly act as repressors of transcription. One member of the family of HDACs is represented by sirtuins, which are deacetylases dependent on NAD+, and, thus, their activity is considered to be related to the physiological stage of the cells. This property makes sirtuins good regulators during environmental changes. However, only a few examples exist, and with differences in the extent of the implication of the role of sirtuins during fungal phytopathogenesis. In this work, we have performed a systematic study of sirtuins in the maize pathogen Ustilago maydis, finding Sir2 to be involved in the dimorphic switch from yeast cell to filament and pathogenic development. Specifically, the deletion of sir2 promotes filamentation, whereas its overexpression highly reduces tumor formation in the plant. Moreover, transcriptomic analysis revealed that Sir2 represses genes that are expressed during biotrophism development. Interestingly, our results suggest that this repressive effect is not through histone deacetylation, indicating a different target of Sir2 in this fungus.